Formula for Success - A. V. Navrotskiy (Высшее образование в России)
The article is devoted to the 90th anniversary of the Volgograd State Technical University (VSTU). The author views the components of the success formula of the University as a flagship University of the Volgograd region, and dwells on the historical facts of the creation of the Stalingrad tractor-building Institute at the beginning of the country’s industrialization and its development to a flagship University, which is a modern multi-campus University with a promising educational, scientific and industrial infrastructure. The article also presents the scientific schools of well-known scientists of the University that carry out fundamental and applied scientific research as well as the international activities of the University, including international cooperation in research, creation and modernization of educational programs, and export of educational services. In its multi-faceted activities, the flagship University focuses on solving urgent problems of socio-economic development of the region. The hybrid model of the flagship University is focused mainly on two typical models: «multi-disciplinary regional University» and «technology leader in the region». The article considers a number of systemic and structural transformations of the University in the framework of a hybrid model: an effective management system for supporting innovation, including socio-psychological attitudes and infrastructure changes; the development of additional education and the creation of conditions for business development.